2010
DOI: 10.18438/b8c61m
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure Reading Among First-Year University Students

Abstract: Objectives – This study examines the reading habits and experiences of first-year undergraduate students at Dalhousie University and the University of King’s College in Halifax, Nova Scotia, Canada. Methods – First-year undergraduate university students (aged 18 to 20) were recruited to take part in focus group discussions and responses were analysed to examine the following topics: (1) the role of reading in their lives, both academic and personal; (2) the development of reading habits from chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Despite the fact that the study focuses on public libraries, its findings will be of interest not only to public but also any librarian tasked with the selection and acquisition of translated fiction, reference and RA librarians in any type of library, Library and Information Science (LIS) students and anyone interested in access to translated fiction. Academic librarians should also find this article particularly relevant because academic libraries have traditionally hosted substantial collections of translated fiction to facilitate their language and literature courses and to support their faculty research and because the practice of RA has enjoyed growing popularity in academia (Cain, 2002;Gilbert and Fister, 2011;Gladwin and Goulding, 2012;Parlette and Howard, 2010;Smith and Young, 2008). The fact that this study focuses on Canadian libraries by no means limits its usefulness to librarians working in the USA and elsewhere.…”
Section: The Problem Statementmentioning
confidence: 99%
“…Despite the fact that the study focuses on public libraries, its findings will be of interest not only to public but also any librarian tasked with the selection and acquisition of translated fiction, reference and RA librarians in any type of library, Library and Information Science (LIS) students and anyone interested in access to translated fiction. Academic librarians should also find this article particularly relevant because academic libraries have traditionally hosted substantial collections of translated fiction to facilitate their language and literature courses and to support their faculty research and because the practice of RA has enjoyed growing popularity in academia (Cain, 2002;Gilbert and Fister, 2011;Gladwin and Goulding, 2012;Parlette and Howard, 2010;Smith and Young, 2008). The fact that this study focuses on Canadian libraries by no means limits its usefulness to librarians working in the USA and elsewhere.…”
Section: The Problem Statementmentioning
confidence: 99%
“…Lack of time management skills -When students enter the academia they are forced to cope with numerous requirements and must divide their time among their various academic assignments. Parlette (2010) found that students mainly read for reasons of usefulness. Students spend more time performing academic assignments than reading non-academic materials.…”
Section: Obstacles To Academic Readingmentioning
confidence: 99%
“…2. Develop habits of learning, reasoning, and methodical work -Reading texts helps students improve the quality of their reasoning, promotes academic reasoning, and teaches students new principles and concepts that can be used to cope with the challenges of the global academic world (Parlette, 2010). 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study also found that students in the Arts and Humanities used the library at a much greater rate than their counterparts in . Parlette and Howard (2010) studied the recreational reading habits of freshman students at two Canadian universities and concluded that reading for pleasure is a wellestablished habit amongst many first-year undergraduate students. First-year undergraduates primarily read for pleasure in order to relax but also recognized that pleasure reading could play a positive role in their academic performance, enhancing their range of background knowledge as well as their active vocabulary.…”
Section: Literature Reviewmentioning
confidence: 99%